Bioremediation of contaminated soil and groundwater by in situ biostimulation - Romantschuk, Martin; Lahti-Leikas, Katariina; Kontro, Merja; Galitskaya, Polina; Talvenmäki, Harri; Simpanen, Suvi; Allen, John A.; Sinkkonen, Aki (Frontiers in Microbiology, 2023)
Bioremediation by in situ biostimulation is an attractive alternative to excavation of contaminated soil. Many in situ remediation methods have been tested with some success; however, due to highly variable results in realistic field conditions, they have not been implemented as widely as they might deserve. To ensure success, methods should be validated under site-analogous conditions before full scale use, which requires expertise and local knowledge by the implementers.The focus here is on indigenous microbial degraders and evaluation of their performance. Identifying and removing biodegradation bottlenecks for degradation of organic pollutants is essential. Limiting factors commonly include: lack of oxygen or alternative electron acceptors, low temperature, and lack of essential nutrients. Additional factors: the bioavailability of the contaminating compound, pH, distribution of the contaminant, and soil structure and moisture, and in some cases, lack of degradation potential which may be amended with bioaugmentation. Methods to remove these bottlenecks are discussed. Implementers should also be prepared to combine methods or use them in sequence. Chemical/physical means may be used to enhance biostimulation. The review also suggests tools for assessing sustainability, life cycle assessment, and risk assessment. To help entrepreneurs, decision makers, and methods developers in the future, we suggest founding a database for otherwise seldom reported unsuccessful interventions, as well as the potential for AI to assist in site evaluation and decision-making.